Robot-assisted partial nephrectomy: Is it the future of kidney surgery? A comparison of nephron-sparing techniques in partial nephrectomy - Ast, Bartłomiej; Piotrowski, Igor; Dobrzeniecki, Krzysztof (Quality in Sport, 2024)
Technological advancements are significantly transforming various medical fields, including urology. The increasing adoption of minimally invasive surgical techniques and robotic assistance is particularly impactful. Three partial nephrectomy techniques are investigated: open partial nephrectomy, laparoscopic partial nephrectomy, and robot-assisted partial nephrectomy. Among these, robot-assisted partial nephrectomy is considered to be superior due to shorter warm ischemia time, reduced blood loss, better early renal functional preservation, and shorter hospital stays. The zero-ischemia partial nephrectomy concept aims to improve postoperative kidney function outcomes. The integration of robotic technology and advancements in artificial intelligence and surgical training systems are expected to further enhance surgical techniques. Artificial intelligence, particularly when combined with computer vision algorithms, shows potential for creating precise and automated three-dimensional models for surgical planning in complex robot-assisted partial nephrectomy procedures, potentially leading to better patient outcomes. This review identifies the current capabilities and prospective advancements in the application of robotic technology in partial nephrectomy.